2011
DOI: 10.1186/1471-2229-11-181
|View full text |Cite
|
Sign up to set email alerts
|

Activation of violaxanthin cycle in darkness is a common response to different abiotic stresses: a case study in Pelvetia canaliculata

Abstract: BackgroundIn the violaxanthin (V) cycle, V is de-epoxidized to zeaxanthin (Z) when strong light or light combined with other stressors lead to an overexcitation of photosystems. However, plants can also suffer stress in darkness and recent reports have shown that dehydration triggers V-de-epoxidation in the absence of light. In this study, we used the highly stress-tolerant brown alga Pelvetia canaliculata as a model organism, due to its lack of lutein and its non-photochemical quenching independent of the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 52 publications
3
55
0
1
Order By: Relevance
“…However, it is interesting to note that Fernández‐Marín et al . (, ) also found that the enzyme violaxanthin de‐epoxidase was activated in the lichen, Lobularia pulmonaria , and in the brown seaweed, Pelvetia canaliculata , in the dark in response to desiccation or high temperature. Furthermore, violaxanthin de‐epoxidation was also induced in response to heat stress at very low irradiation (12 μ mol photons m −1 ·s −1 ) in wheat seedlings (Ilik et al .…”
Section: Discussionmentioning
confidence: 88%
“…However, it is interesting to note that Fernández‐Marín et al . (, ) also found that the enzyme violaxanthin de‐epoxidase was activated in the lichen, Lobularia pulmonaria , and in the brown seaweed, Pelvetia canaliculata , in the dark in response to desiccation or high temperature. Furthermore, violaxanthin de‐epoxidation was also induced in response to heat stress at very low irradiation (12 μ mol photons m −1 ·s −1 ) in wheat seedlings (Ilik et al .…”
Section: Discussionmentioning
confidence: 88%
“…These possible alterations in the chloroplast may include changes in the lipid composition of the thylakoids, in the luminal pH (i.e. by chlororespiration) and/or in the redox state of luminal proteins (Fernández‐Marín et al , , Gasulla et al , Kang and Wang ). Our results demonstrated that significant reductions in F v / F m consistently occurred in response to freezing R. myconi leaves in darkness, although the extent of the reduction of F v / F m was highly variable (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly known that Ddx, as well as Vx, de‐epoxidation depends on high light illumination. However, Fernández‐Marín, Míguez, Becerril, and García‐Plazaola () have shown that Vx de‐epoxidation also occurs in darkness. In Pelvetia canaliculata , a highly stress‐tolerant brown alga, de‐epoxidation was induced by high temperature and other factors such as immersion, anoxia, and dehydration.…”
Section: Discussionmentioning
confidence: 99%